2018
DOI: 10.7150/thno.25308
|View full text |Cite
|
Sign up to set email alerts
|

Targeting S1PR1/STAT3 loop abrogates desmoplasia and chemosensitizes pancreatic cancer to gemcitabine

Abstract: Rationale: Pancreatic cancer is associated with poor prognosis with a 5-year survival rate of less than 6%. Approximately 90% of pancreatic cancer patients harbor somatic mutations in the KRAS gene. Multiple lines of evidence suggest a persistent activation of STAT3 in KRAS-driven oncogenesis contributing to desmoplasia and gemcitabine resistance. Sphingosine 1-phosphate receptor 1 (S1PR1) is an integral component of tumor progression and maintains an activated state of STAT3. FTY720 is an approved drug for mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…It has also been reported that STAT3 regulated expression of S1PR1. Not only can STAT3 mediate S1PR1 expression, but S1PR1 activates STAT3 through the Jak2 tyrosine kinase [24,37,38]. We speculate that Gal-1 activates S1PR1 via activation of an "H-Ras -MEK/ERK -STAT3/S1PR1" axis in GC.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that STAT3 regulated expression of S1PR1. Not only can STAT3 mediate S1PR1 expression, but S1PR1 activates STAT3 through the Jak2 tyrosine kinase [24,37,38]. We speculate that Gal-1 activates S1PR1 via activation of an "H-Ras -MEK/ERK -STAT3/S1PR1" axis in GC.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor STAT3 is overexpressed in multiple cancer types and modulates the expression of genes involved in cell proliferation, survival and differentiation . Furthermore, STAT3 activation confers cancer cell resistance to anti‐cancer drugs such as trastuzumab and cisplatin, and targeting STAT3 is a potential strategy for sensitizing cancer cells to chemotherapy agents . STAT3 signalling is also implicated in mediating resistance to EGFR‐TKI therapy, and targeting STAT3 in conjunction with the EGFR results in enhanced antitumour activity .…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, STAT3 activation confers cancer cell resistance to anti-cancer drugs such as trastuzumab and cisplatin, and targeting STAT3 is a potential strategy for sensitizing cancer cells to chemotherapy agents. [24][25][26][27] STAT3 signalling is also implicated in mediating resistance to EGFR-TKI therapy, and targeting STAT3 in conjunction with the EGFR results in enhanced antitumour activity. 28 Thus, we hypothesized that targeting the upstream activators of STAT3 might be an attractive strategy to overcome EGFR-TKI resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The membranes were blocked with 5% skim milk and antibodies were added and incubated overnight at 4°C. HRP conjugated secondary antibodies were added and immunopositive bands visualized by chemiluminescence . The source of antibodies as follows.…”
Section: Methodsmentioning
confidence: 99%